2022
DOI: 10.3389/fcvm.2022.869168
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Outcomes in Acute Myocardial Infarction Patients Without Standard Modifiable Risk Factors: A Multiethnic Study of 8,680 Asian Patients

Abstract: BackgroundAn increasing proportion of patients with acute myocardial infarction (AMI) are presenting without standard modifiable risk factors (SMuRFs) of hypertension, hypercholesterolemia, diabetes, and smoking, but with an unexpectedly increased mortality. This study examined the SMuRF-less patients presenting with AMI in a multiethnic Asian population.MethodsWe recruited patients presenting with AMI from 2011 to 2021 and compared the prevalence, clinical characteristics, and outcomes of SMuRF-less and SMuRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
(63 reference statements)
8
24
1
1
Order By: Relevance
“…The prevalence of SMuRF-less status in cardiovascular disease seems to range from 3 to 27% depending on the studied population (2, 5-7, 9, 14, 17-19). Our findings concur with existing literature, demonstrating that roughly 1 out of 10 patients who presented with ACS without any prior history of cardiovascular disease had no SMuRFs (2,7,17,20,21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of SMuRF-less status in cardiovascular disease seems to range from 3 to 27% depending on the studied population (2, 5-7, 9, 14, 17-19). Our findings concur with existing literature, demonstrating that roughly 1 out of 10 patients who presented with ACS without any prior history of cardiovascular disease had no SMuRFs (2,7,17,20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our study adds to the growing body of literature that SMuRF-less patients with ACS suffer from excess early all-cause mortality risk (either in-hospital or at 30 days of follow-up) (5)(6)(7)21); yet the long-term post-ACS clinical course did not differ significantly among patients with and without SMuRFs of our study, which also concurs with some of the published reports (7,17). Interestingly, Figtree et al showed that the events contributing to higher all-cause mortality in SMuRF-less patients occurred in the first 30 days; yet allcause mortality remained increased in the SMuRF-less group at a 8-year patient follow-up (7).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent to this study, an analysis of Asian T1AMI cohort showed SMuRF-less patients were younger compared to their counterparts [18]. The study proposed genetic risk could be a factor resulting in earlier presentation of AMI in SMuRF-less patients [18].…”
Section: Discussionsupporting
confidence: 82%
“…The majority of studies on T1AMI cohort have shown SMuRF-less patients are either a similar age or older than SMuRF patients [2,3,5,16,20]. Consistent to this study, an analysis of Asian T1AMI cohort showed SMuRF-less patients were younger compared to their counterparts [18]. The study proposed genetic risk could be a factor resulting in earlier presentation of AMI in SMuRF-less patients [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation